On the complementarity of DNA barcoding and morphology to distinguish benign endemic insects from possible pests: the case of Dirioxa pornia and the tribe Acanthonevrini (Diptera: Tephritidae: Phytalmiinae) in Australia. (8th May 2020) - Martoni, Francesco; Valenzuela, Isabel; Blacket, Mark J.
Abstract: Fruit flies are considered economically important insects due to some species being agricultural pests. However, morphological identification of fruit fly adults and larvae can be difficult requiring a high level of taxonomic expertise, with misidentifications causing problematic false‐positive/negative results. While destructive molecular techniques can assist with the identification process, these often cannot be applied where it is mandatory to retain a voucher reference specimen. In this work, we non‐destructively (and partial‐destructively) processed larvae and adults mostly belonging to the species Dirioxa pornia (Walker, 1849), of the poorly studied nonpest fruit fly tribe Acanthonevrini (Tephritidae) from Australia, to enable molecular identifications whilst retaining morphological vouchers. By retaining the morphological features of specimens, we confirmed useful characters for genus/species‐level identification, contributing to improved accuracy for future diagnostics using both molecular and morphological approaches. We provide DNA barcode information for three species of Acanthonevrini known from Australia, which prior to our study was only available for a single species, D. pornia . Our specimen examinations provide new distribution records for three nonpest species: Acanthonevroides variegatus Permkam and Hancock, 1995 in South Australia, Acanthonevroides basalis (Walker, 1853) and D. pornia in Victoria, Australia; as well as new host plant records for D. pornia, from kangaroo apple, apricot and loquat.